Changing ethnic identities among the Kuy in Cambodia: Assimilation, reassertion and the making of Indigenous identity. (December 2013) - Swift, Peter
Abstract The Kuy are one of the largest Indigenous groups in Cambodia. Though they are extremely similar to the Khmer in terms of physical appearance and material culture, a significant distinction between the two groups continues to be maintained. At the same time, assimilation into the Khmer identity has been a dominant trend among the Kuy for a considerable time and appears to be related to the relatively lower status of the Kuy identity. However, over the past decade or more, some people have begun to reassert a Kuy identity, driven by awareness of benefits of identifying as Kuy and a lessening of the stigmatisation of the Kuy identity. Following the introduction in Cambodia of the concept of Indigenous Peoples, 'Indigenous' has become an ethnic identity that more and more Kuy are assuming and within which they are becoming prominent. It is associated with a broader Indigenous community inside and outside of Cambodia which is becoming increasingly respected. The Indigenous identity has been able to inspire pride and confidence in a way that the Kuy identity has not and has played an important role in letting people of Kuy ancestry 'become Kuy'.